∑ 4 * 5^(i-1) = 4 + 20 + 100 + 500 = 624
∑ 3 * 4^(i-1) = 3 + 12 + 48 + 192 + 768 = 1,023
∑ 5* 6^(i-1) = 5 + 30 = 35
∑ 5^(i-1) = 1 + 5 + 25 + 125 = 156
Answer:
∑ (i=1, 2) 5 * 6^(i-1) < ∑ (i=1, 4) 5^(i-1) < ∑ (i=1, 4) 4 * 5^(i-1) <
< ∑ (i=1, 5) 3 * 4^(i-1)
The answer is a because when u divide that number by 6 u get a whole number
Answer:
y=-(4x/3) -1
Step-by-step explanation:
Slope=m= -4/3
y intercept = c = -1
now using equation;
y= mx+c
y= (-4/3)x+(-1)
y=-(4x/3) -1
Answer:
<AED
Step-by-step explanation:
Ima be real I cant really explain but i think that's right